PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL STRESS KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KONTRAK PROYEK - rosalendro eddy nugroho (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
Companies engaged in the field of construction services usually get a job in the form of project implementation, an activity that produces something that is unique. This activity is temporary and very time-limited, and often not continuous. From this condition it can be understood if most (> 75%) employees in construction service companies are employees of inter-time contracts that will expire their contracts when the project is completed. This study aims to determine the Effect of Work Stress, Leadership Style, and Organizational Culture on Employee Performance Contract Project at PT. Jaya Construction MP.This study was conducted on employees of 98 contract employees in Jakarta project from the number of employees in Jakarta 686 employees. Furthermore, the analysis is done by multiple regression after previou test instruments and test data The results showed that simultaneously three independent variables have a controller of 35.1%, From the results of partial tests obtained the result that organizational culture has a weak influence, work stress moderate and force influence leadership strongly influenced it is suggested that the company more socialize the organization culture to all employees, especially employees of the project contract, the company must also have a way to reduce work stress